(untitled) (Journal of Medicine, 2017)
Background: Beta-Thalassaemia Trait (β-TT) is common in this subcontinent as well as Bangladesh. 3% of our total population is documented to have β-TT. Iron deficiency anemia (IDA), remains one of the most severe and important nutritional disorder in the world especially in Bangladesh. Microcytic hypochromic blood picture is common manifestation of both disorders. Purpose of the present study was to see whether both can co-exist. Methods: This was a cross sectional study carried out in Department of Internal Medicine, Bangabandu Sheikh Mujib Medical University (BSMMU), Dhaka from January-2014 to August-2015. Total 54 participants were selected from Haematology outpatient department (OPD), BSMMU. All of them had β-TT confirmed by Capillary Haemoglobin Electrophoresis. Proper counseling was done and informed consent was taken. Relevant history was taken and examination was done. Five ml of venous blood was collected and sent to Biochemistry department to measure serum iron, ferritin and tissue iron binding capacity (TIBC). Transferrin saturation (T.Sat) was calculated by formula (iron/TIBC) X100. Results: Total 54 patients who fulfilled the recruitment criteria were finally analyzed. Among them 85% (46) patients were females and 15% (8) were males. Median age was 30 years (range11-80 yrs). Most of the patients 78 % (42) belong to the age group between 15 to 44 years. Mean (±SD) HbA2 (%) was 5.35 (±1.39), Hb (%) 9.04± (1.39), MCV (fl)- 67.02 (±10.39), MCH (pg)- 21.06 (±3.99), RDW (%)- 17.77 (±3.85). Among them 44.4% (24) had low iron (<40μg/dl), 29.6 % (16) had low ferritin (15μgm/L), 33.3% (18) had high TIBC (>407μg/dl), and 50% (27) had low transferrin saturation (<16%). 13% (7) patients were found to be iron deficiency considering all parameters and 63% (34) patients were iron deficient in at least one parameter. Conclusions: The present study shows the frequent occurrence of iron deficiency (29.6%) in subjects with β-TT which is a potentially correctable clinical condition. Proper assessment of iron level among the β-TT should be done and those who are iron deficient, should be treated promptly which may improve their general wellbeing. J MEDICINE Jan 2018; 19 (1) : 44-48